Protective effect inhibiting the expression of miR-181a on the diabetic corneal nerve in a mouse model. (March 2020) - Hu, Jianzhang; Huang, Yurong; Lin, Yi; Lin, Jingqiong
Abstract: To investigate the protective effect of inhibiting miR-181a on diabetic corneal nerve in mice, we chose male C57BL/6 mice with streptozotocin (STZ) -induced diabetes as animal models. The expression of miR-181a in trigeminal ganglion tissue (TG) of diabetic mice was detected by real-time PCR. In vitro, we cultured mouse trigeminal ganglion neurons and measured the neuronal axon growth when treated under miR-181a antagomir and negative conditions (NTC). Immunofluorescence showed a significant increase in neuronal axon length in trigeminal ganglion cells treated with miR-181a antagomir. In animal models, we performed epithelial scraping and subconjunctival injection of the miR-181a antagomir and miRNA antagomir NTC to observe the corneal nerve repair by corneal nerve staining. miR-181a antagomir subconjunctival injection significantly increased the corneal epithelium healing of diabetic mice compared with that of the NTC group. Meanwhile, corneal nerve staining showed that the repair of corneal nerve endings was significantly promoted. As the targets of the 181a, ATG5 and BCL-2 were previously identified. The results of Western blot showed that the expression of autophagy associated protein ATG5 and LC3B-II and the expression of anti-apoptotic protein Bcl-2 were decreased in the high-glucose cell culture environment and the diabetic TG tissue. The expression of ATG5, LC3B-II and Bcl-2 were significantly increased after miR-181a antagomir treatment compared with negative control group. This study showed that inhibition of miR-181a expression in diabetic mice could increase ATG5-mediated autophagic activation, BCL-2-mediated inhibition of apoptosis, and promote the growth of trigeminal sensory neurons and the regeneration of corneal nerve fibers. It has a protective effect on diabetic corneal neuropathy. Highlights: We evaluated the expression of miR-181a, which is significantly different between normal and diabetic mice, in trigeminal ganglion tissue. The target genes of miR-181a were predicted by bioinformatics software; Atg5 and Bcl-2 were identified as potential targets. This study demonstrated that inhibiting the expression of miR-181a in a diabetic mouse models can increase Atg5-mediated activation of autophagy and the Bcl-2-mediated inhibition of apoptosis, which has a protective effect.